Transformations through Proximity Flying: A Phenomenological Investigation - Holmbom, Maria; Brymer, Eric; Schweitzer, Robert D. (Frontiers in Psychology, 2017)
Participation in extreme sports has been linked to personal transformations in everyday life. Descriptions of lived experience resulting from transformative experiences are limited. Proximity flying, a relatively new discipline involving BASE jumping with a wingsuit where participants fly close to solid structures, is arguably one of the most extreme of extreme sports. The aim of this paper, part of a larger phenomenological study on the lived experience of proximity flying, is to explicate the ways in which participating in proximity flying influences the everyday lives of participants. Interpretative phenomenological analysis was used to explicate the lived experience of six proximity pilots. An analysis of interview transcripts revealed three significant themes describing the lived experience of participants. First, experiences of change were described as positive and skills developed through proximity flying were transferrable into everyday life. Second, transformative experiences were considered fundamental to participants’ perspectives on life. Third, experience of transformation influenced their sense of personal identity and facilitated flourishing in other aspects of everyday life. Participants were clear that their experiences in proximity flying facilitated a profound process of transformation which manifest as changes in everyday capabilities and behaviours, values and sense of identity.